Choosing, Doing, and Controlling: Implicit Sense of Agency Over Somatosensory Events. (July 2017) - Borhani, Khatereh; Beck, Brianna; Haggard, Patrick
Sense of agency—a feeling of control over one's actions and their outcomes—might include at least two components: free choice over which outcome to pursue and motoric control over the action causing the outcome. We orthogonally manipulated locus of outcome choice (free or instructed choice) and motoric control (active or passive movement), while measuring the perceived temporal attraction between actions and outcomes ( temporal binding ) as an implicit marker of agency. Participants also rated stimulus intensity so that we could measure sensory attenuation, another possible implicit marker of agency. Actions caused higher or lower levels of either painful heat or mild electrotactile stimulation. We found that both motoric control and outcome choice contributed to outcome binding. Moreover, free choice, relative to instructed choice, attenuated the perceived magnitude of high-intensity outcomes, but only when participants made an active movement. Thus, choosing, not just doing, influences temporal binding and sensory attenuation, though in different ways. Our results show that these implicit measures of agency are sensitive to both voluntary motor commands and instrumental control over action outcomes.